Engagement Pegawai Generasi Millenial: Antara Gaya Komunikasi Pimpinan dan Iklim OrganisasiI - Bambang Kismanto (Pusat Pendidikan dan Pelatihan Perdagangan, 2019)
Employee engagement is important for all parts of human resources in an agency or company. Employees and leaders who are not engaged with the organization had a decrease in the level of work quality, a decrease in efficiency, inconsistencies in service, a decrease in initiatives to provide suggestions for organizational progress, and ultimately reduce the level of organizational performance. Thus it is necessary to explore the factors that can influence the level of employee engagement. Factors of leadership style and organizational climate are examined for their influence on the level of employee engagement in this study which is divided into three hypotheses. The research locus is in the Financial Education and Training Agency. Data analysis in this study was carried out using SPSS version 17.0 for windows. Keywords:Engagement, leader communication style, organization behavior